Linking Process and Outcome Measures to Improve Employment Support Programs for Individuals With the Most Significant Disabilities - Riesen, Tim; Remund, Corban; Snyder, Aubrey (Frontiers in Rehabilitation Sciences, 2022)
Employment agencies and funding systems commonly use distal outcome measures such as employed or not employed, full-time or part-time, and continuous measures such as wage, hours worked, and type of job to document the employment status of individuals with disabilities. These measures continue to demonstrate that individuals with disabilities fall behind individuals without disabilities in all employment outcomes. While there is utility in distal outcome measures, it is difficult to determine what intervention or program variables were responsible for a specific outcome. Moreover, outcome measures do not provide sufficient information about the quality of employment supports and services an individual with disabilities receives. One way to improve accountability in employment support programs is to link outcomes to specific process for obtaining and maintaining employment. The purpose of this manuscript is to describe how employment programs can link short-term (proximal) and long term (distal) outcomes measures to specific process for employment. A customized employment framework is used to illustrate how systematically linking outcomes and process improves accountability in programs that support job seekers with most significant disabilities.